Transform the Paradigm of Conventional to Advanced Cooking Process - Sjukriana, Juke; Falaq, Muhammad (Stupa, 2022)
Hotel Salak The Heritage, a four star hotel in Bogor, has conducted the research for developing and producing spice powder in cooperation with PT AGFI which already exists in Sundanese food industry. The spice powder is produced by using stable pressure, low temperature drying process (50-60°C) and intensive quality controls, which result in low water content and hygienically excellent product, as it is free from bacterial filth and other impurities. Since this product only consists of natural ingredients, it gives a standard flavoring effect and no unwanted colors to the end food product. Hotel Salak has made some experiments on the effectiveness of cooking process using spice powder, one of the examples is Beef Rendang, and saves cooking and preparation time up to 16.7% and saves cost up to 9.36 %. This is expected to change the paradigm of conventional to more effective, efficient and clean cooking process.